Ergonomic Industry Efforts to Prevent Business Failure - Gempur Santoso (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article discusses and discovers ergonomic industrial efforts to prevent losses, aka preventing business failure. This article is designed descriptively. This design uses literature to collect data, namely data from various opinions and research results. Then it is analyzed and discussed using descriptive methods as well. Conclusion: 1. In industrial business work activities, ergonomic performance must be balanced between capacity and work tasks. Ergonomic industrial businesses are able to harmonize human needs, machines, material needs, work/production methods, funding needs and sales capacity in the market; 2. Management must be managed ergonomically, that is, in a balanced/harmonious manner that runs well, thereby preventing business failure. With an ergonomic approach, your business will be sustainable. Suggestion: Harmonious application of the 6 M's (man, machine, material, method, money, marketing) in new or existing businesses must be implemented to avoid losses